Poverty Profile and Poverty Measurement Technique of Nepal - Kumar, Nand Kishor (PYC Nepal Journal of Management, 2019)
Poverty measurement is necessary for making anti-poverty policy and social spending policy in a rapidly changing economic environment. Cost of basic needs (CBN) method is the widely used in Nepal for measuring poverty line. The main objective of this paper is to evaluate the poverty profile of Nepal and to assess the practices of poverty measurement of Central Bureau of Statistics in Nepal. This study has employed descriptive method of analysis. The major conclusion of this study is that the poverty situation of the Nepal is declining. It also suggests that during the evaluation of poverty line in every survey, the new poverty line should incorporate calorie requirement for changing lifestyle and taste of human’s increasing wants.